An Investigation of Currency Forecasting with Particular Emphasis on the UK and China - Pang, Ying (2006)
This paper compares a number of models on the basis of their accuracy in forecasting the future value of the RMB and British Pound sterling for six months, one- year and two-year horizons. Purchasing power parity, uncovered interest parity and expectation theory are considered in the paper. Forecasts derived from the forecast techniques will be compared with the actual exchange rates movements. In general, under fundamental analyses, all of the results for forecasting the value of RMB and pound sterling are both disappointing.